LEGAL PROTECTION REGULATIONS FOR FOREIGN WORKERS WITH PROFESSIONAL EXPERTISE CERTIFICATIONS - Putra, Aldo Ernandi; Tan, Winsherly; Syarief, Elza (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
ABSTRACTThis research explores the legal safeguards provided to foreign workers (TKA) who possess certified professional expertise, and how their presence influences local labor (TKL) in Batam City, with a case study of two companies: PT VME and PT NSP Technology. The growing presence of foreign professionals in key positions has raised questions about the effectiveness of existing labor laws in ensuring fairness and protection for Indonesian workers. Using an empirical legal research method, the study relies on interview data and field observations. The analysis is framed by the Theory of Legal Benefit and the Theory of Legal Effectiveness. The results indicate that current regulations particularly the Job Creation Law and Government Regulation No. 34 of 2021 have yet to adequately limit the dominance of foreign workers. This ineffectiveness stems from company preferences for international labor standards, relaxed internal policies, and weak regulatory oversight. In light of these findings, the study suggests the need for firmer regulatory measures to control the number and positions of foreign employees while simultaneously enhancing the competitiveness of local workers through targeted training and skill certification aligned with industrial requirements.